Random Fixed Point Theorems of Random Comparable Operators and an Application. (9th March 2015) - Yin, Jiandong; Liu, Zhongdong
Abstract : We introduce the new concept of random comparable operators as a generalization of random monotone operators and prove several random fixed point theorems for such a class of operators in partially ordered Banach spaces. Part of the presented results generalize and extend some known results of random monotone operators. Finally, as an application, we consider the existence of the solution of a random Hammerstein integral equation.